Taylor e Walzer e a política de reconhecimento: meios de inclusão dos grupos sócio-culturais ao status de exercício da cidadania - Toss, Luciane Lourdes Webber (Universidade do Vale do Rio do Sinos, 2006)
This study is an attempt to use TAYLOR’s and WALZER’s communitarian theory to redefine the concept of citizenship, through the possibility of acceptable procedures and moral limits which may contribute for the inclusion of a politics of recognition as a propositional element in public policies, concerning disadvantaged social and cultural groups in the processes of distribution and accessibility of goods in the public space. The study was developed based on bibliographic research on the works of the two authors, trying to pinpoint: I – what communitarian assumptions can be found in TAYLOR and WALZER; II – what the main categories and concepts of the two authors are, as well as the possibilities of convergence and divergence between them; III – what the moral limits and the acceptable procedures are, as well as the relation between those and the politics of recognition. In order to discuss the politics of recognition, authors such as HABERMAS, FRASER, HONNETH, SORIANO DIAZ, and THIEBAUT were used, among others
Keywords: cidadania; igualdade; política de reconhecimento; comunitarismo; citizenship; equality; politics of recognition; communitarianism; Ciências Sociais Aplicadas